Polska! Biało-czerwoni! - Kosiński, Dariusz (Załącznik Kulturoznawczy, 2023)
The article attempts to analyze sport performances as the space and tool of producing and establishing national identity. From this perspective the author interprets the performances by the fans of Polish national volleyball team. They are seen as the effective creations of open and joyful patriotism, opposite to the grave, sacrifical and nationalistic patriotism growing out of the pararitualistic postromantic traditions.